Life-style of Rural Secondary School Children in Bangladesh with Particular Emphasis to Physical Exercise and Diet (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: With rapid improvement of socioeconomic condition of developing countries in the last two decades, a rapid change in the nutritional behaviour and activity of adolescents is evident leading to increased prevalence of overweight and obesity among them. The present cross-sectional survey was undertaken to evaluate the dietary and exercise behavior of the adolescents studying in rural secondary schools.Methods: This study was conducted in the Department of Community Medicine, Rajshahi Medical College, Rajshahi from April-May 2019. Data were collected from secondary schools of Puthia. A total of 535 students from two secondary schools participated in the study. In order to ensure an equal representation from both sexes we chose one boys‟ and one girls‟ schools. Every alternate students of those schools from class VI-X were then included in study as respondents. Weight and height of the selected students were first taken followed by interview.Result: In the present study 15% of the secondary school children were found underweight and 18% were overweight or obese. About 65% of the of the respondents‟ family were more or less financially solvent. Fifty percent of the adolescents reported that they were accustomed to a healthy balanced diet with 45% reportedly taking fruits and 60% taking plenty of vegetables every day. But only 17.3% took 3 or more servings of fruits a day (the minimum recommended fruit intake). Thirty percent of the adolescents were used to having high carbohydrate and fat. In terms of exercise practice, two-thirds (67.3%) of the students had healthy practice. The predominantly practiced exercise was running (65%) followed by cycling (64.4%), playing cricket (63.6%), football (57.2%) and fast walking (52.2%). However, with respect to number of days of exercise in a week and duration of exercise each day a sizable portion of the students‟ practice was not considered an ideal one. The respondents who did not practice any kinds of exercise or sports activities, most frequently mentioned their „preoccupation with coaching or private tutors‟ (79.4%) as reasons of inactivity, followed by non-encouragement about playing by their parents (71.4%) and teachers (65.5%). Nearly 60% were interested to play but they did not have any playing field nearby home. Nearly one-third of the students pass  > 1 hour of their leisure time by watching TV or sitting at computer or playing games or other activities on mobile. Opinion-seeking questionnaire revealed that 20-50% of the respondents had misconception on healthy diet, food, energy-rich food, balanced diet and their ability to make a healthy choice for food in any one of these food & diet-related issues. Boys are more likely to be obese and underweight than the girls.Conclusion: Unhealthy dietary behavior is widespread among secondary school adolescents in rural area. About one-third of the rural secondary school children are physically inactive and predominant reasons of their inactivity are preoccupation with coaching center or private tutors or no incentive for playing from the parents or teachers. The knowledge level of the students on healthy diet and food is not up to the desired level to make healthy choices for food themselves. Both unhealthy dietary behavior & inactivity might have contributed to inappreciably adverse nutritional status of the secondary level school children.Ibrahim Card Med J 2018; 8 (1&2): 39-47